SYSTEMATIC LITERATURE REVIEW OF BIM ASSESSMENT MODELS FOR BIM-BASED PROJECTS - Wan Nur Syazwani Wan Mohammad (International Journal of Accounting, Finance and Business, 2022)
Building Information Modeling (BIM) is an important technology enabler for digitaltransformation in construction. It is a highly collaborative process that allows architects,engineers, contractors and other construction professionals to plan, design and construct abuilding or facility in the form of a 3D model-base. Recently, various BIM assessment modelshave been established either from developed and developing countries to assess the BIMperformance for construction professionals and BIM-based projects. Nevertheless, theadoption level of BIM among construction professionals in developing countries, particularlyMalaysia remains lower than expected. Hence, the aim of this paper is to explore the BIMassessment model either from developed and developing countries via Systematic LiteratureReview (SLR). Subsequently, it is to determine the trends and key elements from the identifiedmodels. A Systematic Literature Review (SLR) was conducted on BIM assessment modelarticles published in three databases (i.e., Web of Science, Science Direct and Scopus) from2007 until 2019. The results revealed that BIM assessment models from developed countrieswere dominant compared to developing countries. These models also vary according to theirassessment framework and evaluation mechanisms. Other than that, the results also highlightedfour (4) main elements from the BIM assessment models. These are; BIM objectives, BIM uses,BIM adoption components and project performance criteria’s’. Thus, the study provides apositive insight of the practitioners either from developed and developing countries to beconsidered in the trends and key elements while assessing BIM in their projects.